The Power of Apotropaion. Not only about ancient reminiscences in medieval weaponry from Polish lands - Arkadiusz Michalak (In Gremium. Studies in History, Culture and Politics, 2020)
Shield surfaces have been decorated since ancient times. The motif often repeated in their decorations were images of evil eyes, monsters, mythical animals (signa horribilia). Depiction from the shield increased apotropeically, the protective properties of the shield. A popular face motif also appearing on the shields at that time was also the emblem of the lions, or figures with stylized animal ears, evoking an association with the figure of a mythological satire and the personification of celestial bodies: the Sun and the Moon. On the altars created in Bohemian workshops, we also find deciduous or planted masks with floral motifs on the shields, which are interpreted as a representation of a wild man.Until today the only known shield with a similar motif from Polish lands came from the scene of the Crucifixion of Christ depicted on frescoes from the church of St. Marcin in Wichów, near Żagań, dated to the second quarter of the 15th century (Fig. 1: 1). In the article we discuss the next depiction from the Crucifixion scene: contained in the Brewery from around 1420, the Collegiate Library in Głogów, University Library (reference number IF 442) (Fig. 1:3), from the Bible Sacra Veteri et Novi Testamenti (the so-called Bible of Banks), from circa 1427 (St. B, R. 162) (Fig. 1:4), frescoes from the Holy Trinity chapel at the Lublin castle (Fig. 1: 2) and from the figural lodging of the Resurrection of the altar from Brodnica (Śrem county), dating back to the beginning of the 16th century.Protective representation of the face is another motif with ancient roots, which found its place in the culture of the Middle Ages and the decoration of medieval arms and armour.